Solving Magnetohydrodynamic Stagnation-Point Flow Towards a Stretching/Shrinking Sheet using bvp4c Solver - Mohd Nazri , Muhamad Salman; Aman, Fazlina (Enhanced Knowledge in Sciences and Technology, 2025)
Magnetohydrodynamic (MHD) flows involve the interaction between magnetic fields and electrically conductive fluids, frequently observed in various natural and industrial processes. The governing equations for MHD stagnation-point flow towards a stretching/shrinking sheet are transformed into ordinary differential equations via similarity transformation and solved numerically using the bvp4c solver in MATLAB. Results reveal that an increase in thermal slip and velocity slip parameters leads to a reduction in heat transfer rates, while stronger magnetic field strength decreases the fluid velocity near the sheet but enhances the boundary layer thickness. These findings provide valuable insights for engineering applications, including heat transfer systems and aerodynamic flow control.